A method for generating single metalloprotein crystals in well-defined redox states: combined electrochemical control and infrared microspectroscopic imaging of a NiFe hydrogenase crystal - Ash, P; Carr, S; Reeve, H; Rowbotham, J; Shutt, R; Frogley, M; Evans, R; Cinque, G; Armstrong, F; Vincent, K (Royal Society of Chemistry, 2017)
We describe an approach to generating and verifying well-defined redox states in metalloprotein single crystals by combining electrochemical control with synchtroton infrared microspectroscopic imaging. For NiFe hydrogenase 1 from Escherichia coli we demonstrate fully reversible and uniform electrochemical reduction from the oxidised inactive to the fully reduced state, and temporally resolve steps during this reduction.